Assessing the English-speaking Community's Capacity to Access Arts, Culture, and Heritage in Nine Regions of Quebec : A Report on Phase One of the "Enhancing Access to Cultural Expression" Project (EACE) - Quebec Community Groups Network (QCGN); Palmer, Lise (2010)
In 2008, the Quebec Community Groups Network (QCGN) Board of Directors passed a formal resolution to prioritize the development of the Arts, Culture and Heritage sector. This area was prioritized by a majority of members in the Network and was supported by the Board. An Arts, Culture and Heritage working group was created to develop a policy framework in this area to streamline and guide the activities of the Network. The main partners in this endeavour were the English Language Arts Network (ELAN) represented by Guy Rodgers, the Quebec Anglophone Heritage Network (QAHN) represented by Kevin O'Donnell and Dwane Wilkin and the QCGN represented by Sylvia Martin-Laforge. Jane Needles also participated in the working group representing both the QCGN and ELAN. The policy framework, which was completed in November 2008, identified key areas of intervention over the next five years to support the dynamic growth and development of the cultural expression of English-speaking Quebec. The first was a project to access cultural expression through expanded partnerships. This current project “Enhancing Access to Cultural Expression” is a direct result of the prioritization of access to cultural expression. The other areas of priority included recognition and support through visibility - which is currently being addressed through the RAEV project being implemented by ELAN - and the creative economy - an issue yet to be addressed.

[Letter to Premier Couillard re: English Schools / Lettre au premier ministre Couillard concernant les écoles anglaises] - Quebec Community Groups Network (QCGN) (2015)